Irish nationalists and the making of the Irish race - Nelson, Bruce, 1940-2022 (Princeton University Press, 2012)
This is a book about Irish nationalism and how Irish nationalists developed their own conception of the Irish race. Bruce Nelson begins with an exploration of the discourse of race--from the nineteenth--century belief that ""race is everything"" to the more recent argument that there are no races. He focuses on how English observers constructed the "native" and Catholic Irish as uncivilized and savage, and on the racialization of the Irish in the nineteenth century, especially in Britain and the United States, where Irish immigrants were often portrayed in terms that had been applied mainly to enslaved Africans and their descendants.